Minority gangs in Singapore prisons: Prisonisation revisited - Narayanan, Ganapathy (The Australian and New Zealand journal of criminology, 2020)
This article attempts to better contextualise the theoretical and empirical connections between pre-prison orientation of prisoners and their subsequent adaption and subjective experiences of imprisonment using the case study of Omega, a racial minority gang in the Singapore prisons. While the article traces the gang’s emergence to its marginality in both the mainstream and illegitimate societies, the persistence of Omega beyond prisons is also shown to lie in its capacity to be remodelled for the street where the gang operates on an equal footing with the historically entrenched Chinese Secret Societies in the illicit economy. This research is not only able to adequately explain the form and hierarchy of penal subcultures, and the differentiated strategies offered by the various racial, class and gender groups to ‘surviving’ prisons, but also shows how in-prison adaptations affect the construction of post-prison identities and behaviours. The intent is to provide a nuanced sociological examination of the prison institution by capturing the iterative and interactive effects between the ‘outside’ (i.e. street) and the ‘inside’ (i.e. prison), thus extending the analysis beyond the deprivation-importation impasse by introducing an element of ‘exportation’ that help contextualise the racialised experiences of minority prisoners in the postcolonial state.